Stimulating effect of graphene oxide on myogenesis of C2C12 myoblasts on RGD peptide-decorated PLGA nanofiber matrices. Issue 1 (December 2015) - Shin, Yong; Lee, Jong; Kim, Min; Hong, Suck; Kim, Bongju; Hyun, Jung; Choi, Yu; Park, Jong-Chul; Han, Dong-Wook
Abstract Background In the field of biomedical engineering, many studies have focused on the possible applications of graphene and related nanomaterials due to their potential for use as scaffolds, coating materials and delivery carriers. On the other hand, electrospun nanofiber matrices composed of diverse biocompatible polymers have attracted tremendous attention for tissue engineering and regenerative medicine. However, their combination is intriguing and still challenging. Results In the present study, we fabricated nanofiber matrices composed of M13 bacteriophage with RGD peptide displayed on its surface (RGD-M13 phage) and poly(lactic-co -glycolic acid, PLGA) and characterized their physicochemical properties. In addition, the effect of graphene oxide (GO) on the cellular behaviors of C2C12 myoblasts, which were cultured on PLGA decorated with RGD-M13 phage (RGD/PLGA) nanofiber matrices, was investigated. Our results revealed that the RGD/PLGA nanofiber matrices have suitable physicochemical properties as a tissue engineering scaffold and the growth of C2C12 myoblasts were significantly enhanced on the matrices. Moreover, the myogenic differentiation of C2C12 myoblasts was substantially stimulated when they were cultured on the RGD/PLGA matrices in the presence of GO. Conclusion In conclusion, these findings propose that the combination of RGD/PLGA nanofiber matrices and GO can be used as a promising strategy for skeletal tissue engineering and regeneration.